THE EFFECT OF MOTIVATION ON THE WORK PERFORMANCE OF CV. MAKMUR SEJAHTERA - Tommy Saputra; Armansyah, Armansyah (MBISKU: Jurnal Manajemen Bisnis dan Keuangan, 2025)
The purpose of this study is to assess the influence of intrinsic motivation, which consists of achievements achieved, recognition of others, the job itself, opportunities for growth, and responsibility, partially and simultaneously on the work performance of employees on CV. Makmur Sejahtera. The population and sample in this study are all CV employees. Makmur Sejahtera which totals 30 people, using a saturated sampling technique. This study uses multiple regression analysis tools, t-test, and F test to evaluate the influence of intrinsic motivation variables on employee work performance. The results of the test both partially (t-test) and simultaneously (F-test) showed that the intrinsic motivation variable did not have a positive and significant influence on the work performance of employees in CV. Makmur Sejahtera. Thus, it can be concluded that in the context of such companies, intrinsic motivation, which consists of factors such as achievements achieved, recognition of others, the job itself, opportunities for growth, and responsibilities, does not have a significant impact on the employee's work performance.